Zymomonas mobilis Biofilm Reactor for Ethanol Production Using Rice Straw Hydrolysate Under Continuous and Repeated Batch Processes - Todhanakasem, Tatsaporn; Salangsing, O-lan; Koomphongse, Piyawit; Kaewket, Sanya; Kanokratana, Pattanop; Champreda, Verawat (Frontiers in Microbiology, 2019)
Abstract Plastic composited corn silk was developed as a biotic/abiotic carrier for Z. mobilis biofilm formation for the purpose of ethanol production. Furthermore, we explored the use of rice straw hydrolysate as substrate in both multistage continuous culture and repeated batch processes and compared the ethanol production efficiency by two strains of Z. mobilis. Biofilm formed by bacterial strains Z. mobilis ZM4 and TISTR551 were detected and its proficiencies were compared under various conditions by scanning electron microscopy (SEM) and crystal violet assays. The greatest biofilm formed by both strains was found on day five after the inoculation. Z. mobilis strain ZM4 grown in repeated batch biofilm reactors produced higher yields of ethanol than TISTR551 grown under the same conditions, while TISTR551 produced higher yields of ethanol in the multistage continuous process. The yields were highly maintained with no significant differences (p  0.05) among three consecutive repeated batches. These experiments highlight exciting uses for agricultural by-products in the production of ethanol using Z. mobilis biofilm reactors